Simultaneous Determination and Risk Assessment of Pyrrolizidine Alkaloids in Artemisia capillaris Thunb. by UPLC-MS/MS Together with Chemometrics - Li-Hua Chen (Molecules, 2019)
Pyrrolizidine alkaloids (PAs) are natural toxins found in some genera of the family Asteraceae. However, it has not been reported whether PAs are present in the widely used Asteraceae plant Artemisia capillaris Thunb. (A. capillaris). The purpose of this study was to establish a sensitive and rapid UPLC-MS/MS method together with chemometrics analysis for simultaneous determination and risk assessment of PAs in A. capillaris. The developed UPLC-MS/MS method was validated and was confirmed to display desirable high selectivity, precision and accuracy. Risk assessment was conducted according to the European Medicines Agency (EMA) guideline. Chemometrics analysis was performed with hierarchical clustering analysis and principal component analysis to characterize the differences between PAs of A. capillaris. Finally, PAs were found in 29 out of 30 samples and at least two were detected in each sample, besides, more than half of the samples exceeded the EMA baseline. Nevertheless, the chemometrics results suggested that the PAs contents of A. capillaris from different sources varied significantly. The method was successfully applied to the detection and risk evaluation of PAs-containing A. capillaris for the first time. This study should provide a meaningful reference for the rational and safe use of A. capillaris.